2015
DOI: 10.1063/1.4918273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic spins flipping process on the dielectric properties of α-Fe1.6Ga0.4O3 system

Abstract: The α-Fe1.6Ga0.4O3 (Ga doped α-Fe2O3) sample has been stabilized in rhombohedral structure. The sample is a canted ferromagnet at 300 K and above. The spins structure starts flipping from in-plane direction to out of plane direction of the rhombohedral structure to exhibit an antiferromagnetic order below a typical temperature ∼ 215 K, known as Morin transition. The magnetic and dielectric properties of α-Fe1.6Ga0.4O3 system have been discussed in the temperature range 123 K to 350 K to examine the effect of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…C. Papaioannoua et al 10 suggested a possible charge-spin coupling in hematite. Our recent work 11 has highlighted the effect of magnetic spins flipping on magneto-electric coupling in α-Fe 1.6 Ga 0.4 O 3 system. The ferromagnetic semiconductor properties of Ga doped α-Fe 2 O 3 system are not like conventional III-V ions based diluted ferromagnetic semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…C. Papaioannoua et al 10 suggested a possible charge-spin coupling in hematite. Our recent work 11 has highlighted the effect of magnetic spins flipping on magneto-electric coupling in α-Fe 1.6 Ga 0.4 O 3 system. The ferromagnetic semiconductor properties of Ga doped α-Fe 2 O 3 system are not like conventional III-V ions based diluted ferromagnetic semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of spin-lattice coupling and small atomic displacement within rhombohedral structure of Ga doped hematite are indicated from Micro-Raman spectra. The dielectric peak in the temperature regime (290 K-310 K), where Fe 3+ spins started flipping from in-plane direction (canted FM state) to out of plane direction [32,42], indicated (canted) spin order induced magneto-electric coupling in Ga doped hematite system. We restrict our discussion for the origin of electric polarization in Ga doped hematite system based on the models of spin induced ferroelectricity [5,24].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, magnetic coercivity decreased with the increase of Ga content in hematite structure. These features indicated a modified magnetic structure in Ga doped hematite system [29,[31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations